The Effect of TikTok Use on Final Project Concentration in Islamic Guidance and Counseling Students of the 2021 - Luthvi Hafizah; Dika Sahputra (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
This study aims to determine the effect of Tiktok usage on the concentration of completing final assignments among students of Islamic Guidance and Counseling Class of 2021, Faculty of Da’wah and Communication, State Islamic University of North Sumatra. The research method used was descriptive quantitative with an incidental sampling technique. The participants of this study were 53 students. The data were analyzed using simple linear regression with SPSS version 21. The findings indicate that Tiktok usage has a positive and significant impact on students’ concentration in completing their final projects. The coefficient of determination (R²) of 0.581 indicates that 58.1% of the concentration variable can be explained by the Tiktok usage variable, with a strong correlation (R = 0.762). However, the impact greatly depends on usage patterns. When used in a controlled manner and directed toward educational or motivational content, Tiktok can serve as a supporting medium in completing final assignments. Conversely, excessive use without self-control tends to cause distractions and procrastination. Therefore, digital awareness and self-control are important factors for students to use Tiktok wisely in their academic process. Keywords: Tiktok, Concentration, Final Assignment, Students, Social Media Abstrak Penelitian ini menganalisis pengaruh penggunaan Tiktok terhadap tingkat konsentrasi penyelesaian tugas akhir pada mahasiswa Bimbingan dan Penyuluhan Islam Angkatan 2021, Fakultas Dakwah dan Komunikasi di Universitas Islam Negeri Sumatera Utara. Metode studi yang dipakai kuantitatif deskriptif melalui teknik sampling insidental. Jumlah partisipan Penelitian ini sebanyak 53 mahasiswa/i. Data diolah menggunakan regresi linier sederhana melalui SPSS 21. Hasil studi menandakan penggunaan Tiktok berdampak positif dan esensial pada konsentrasi mahasiswa dalam menyelesaikan tugas akhir. Nilai koefisien determinasi (R²) sebanyak 0,581 menandakan 58,1% variabel konsentrasi dapat dijelaskan oleh variabel penggunaan Tiktok, dengan korelasi yang kuat (R = 0,762). Namun dampaknya sangat bergantung pada pola penggunaan. Jika digunakan secara terkontrol dan diarahkan pada konten edukatif atau motivasi, Tiktok dapat menjadi media pendukung dalam menyelesaikan tugas akhir. Sebaliknya, penggunaan berlebihan tanpa pengendalian diri cenderung menyebabkan gangguan fokus dan prokrastinasi. Oleh karena itu, kesadaran digital dan self-control menjadi faktor penting agar mahasiswa dapat memanfaatkan Tiktok secara bijak dalam proses akademik. Kata Kunci: Tiktok, Konsentrasi, Tugas Akhir, Mahasiswa, Media Sosial